The Impact of Technological Advancements in Accounting Information Systems on Achieving Alignment Between Financial Accounting Theory and Practical Application at Jordanian Commercial Banks - Alassuli, Abdalla Hussain Ahmad (International Review of Management and Marketing, 2024)
The study aimed to find out the impact of technological advancements in accounting information systems on achieving alignment between financial accounting theory and practical application at Jordanian commercial banks. The descriptive analytical approach was adopted using the quantitative method to achieve the purpose of the study. A questionnaire tool was constructed to collect data and verify its reliability and stability. A sample of 385 employees of Jordanian commercial banks answered the questionnaire. The results showed that AIS technological progress has a significant impact in achieving alignment between financial accounting theory and practical application in Jordanian commercial banks. All technological dimensions such as the technical dimension, human dimension, organizational dimension, security, environmental and administrative dimensions showed a positive and noticeable impact. It was found that the environmental and technical dimensions had the greatest impact, while the organizational dimension came in last place in terms of impact.